The Giant "Pacifica", Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
Pacifica, eighty feet tall, stands before a scintillating metal curtain above the entrance to the Cavalcade of the Golden West and overlooking the Court of the Seven Seas at San Francisco's 1939 Golden Gate International Exposition.